Establishment of Vision Effect Diagram for Optimization of Smart LED Lighting - Qi Yao; Lei Yuan; Yu Bian (IEEE Photonics Journal, 2016)
In this paper, a diagram illustrating the combined circadian effect and mesopic vision effect caused by cirtopic, scotopic, and photopic photoreceptors, i.e., a vision effect diagram, was established using a chromaticity diagram based on $L$ , $M$ , and $S$ cone cells for reference. The characteristics of the vision effect diagram were studied, and many features were found to be similar to those of the reference chromaticity diagram. The relationship between the vision effect and the chromaticity diagrams was also studied to ensure that the circadian and mesopic vision effects would be present in the desired chromaticity range. The vision effect diagram is a mathematical tool that can be used to calculate and predict circadian and mesopic vision effects of light sources, as well as to optimize light sources to induce these effects. Optimized light sources with both desirable circadian and mesopic vision effects would not only be useful when these two vision effects are stimulated together but would do well in future smart light-emitting diode (LED) lighting with adjustable luminance in many outdoor applications as well.